PENGARUH INDUSTRIALISASI TERHADAP PERGESERAN NILAI SOSIAL PADA MASYARAKAT DESA TEGALREJO KECAMATAN CEPER KABUPATEN KLATEN TAHUN 2012 - Nuridha, Sigit Dwi (Educitizen, 2013)
Considering the data analysis, it could be obtained the rstatistic value = 0.319 and at significance level of 5% with db = n-2=72, because rstatistic > rtable (0.319>0.231), Ha was supported and H0 was not supported meaning that there was a positive effect, while the tstatistic value = 3.015 and significance level of 5% with db = n-2=72, ttable = 1.98, because rstatistic > rtable, Ha was supported and H0 was not supported meaning that there was a significant effect of X on Y variable. From the data analysis above, the hypothesis that ?There was a positive significant effect of industrialization on social value shift in Tegalrejo villagers variable, in Ceper Subdistrict, Klaten Regency in 2012? was supported. The contribution of X effect on Y was 10.2%. It meant that 10.2% social value shift in Tegalrejo villagers of Ceper Subdistrict of Klaten Regency in 2012 was affected by industrialization.Considering the information above, it could be concluded that there was a positive significant industrialization on social value shift in the Tegalrejo villagers of Ceper Subdistrict of Klaten Regency in 2012